Let j(x)=x^2j(x)=x2 and k(x)=x^3k(x)=x3, does k(j(x))=j(k(x))k(j(x))=j(k(x))?

1 Answer
Jan 8, 2017

Yes

Explanation:

k(j(x)) = k(x^2) = (x^2)^3 = x^6 = (x^3)^2 = j(x^3) = j(k(x))k(j(x))=k(x2)=(x2)3=x6=(x3)2=j(x3)=j(k(x))

More generally...

If m, nm,n are positive integers and xx is any number, then we find:

(x^m)^n = overbrace(x^m xx x^m xx ... xx x^m)^"n times"

color(white)((x^m)^n) = overbrace(overbrace((x xx x xx ... xx x))^"m times" xx overbrace((x xx x xx ... xx x))^"m times" xx ... xx overbrace((x xx x xx ... xx x))^"m times")^"n times"

color(white)((x^m)^n) = overbrace(x xx x xx ... xx x)^"mn times"

color(white)((x^m)^n) = x^(mn)

So in particular:

(x^m)^n = x^(mn) = x^(nm) = (x^n)^m

color(white)()
Footnote

(x^m)^n = x^(mn) holds in any of the following circumstances:

  • Any number x (Real or complex), with m, n positive integers.

  • Any non-zero number x (Real or complex), with m, n any integers.

  • Any positive (Real) number x, with m, n any numbers.

It does not hold in all cases.

For example:

-1 = (-1)^1 = (-1)^(3/2*2/3) != ((-1)^(3/2))^(2/3) = (-i)^(2/3) = 1/2-sqrt(3)/2i